The answer to this is x = -2. Here is how to go about doing this problem:

Remember that you are trying to get all the terms that have variables on one side of the equation and all the numbers on the other. We'll start by doing that. You can do that by subtracting 5 from both sides. Then you have

2x - 7x = 10

So now you can simply subtract 7x from 2x. That gives you

-5x = 10

Then, to get a value for x, you divide both sides by -5. That gets you

x = -2

2x + 5 - 7x = 15

First you need to group similar terms:

2x - 7x + 5 = 15

==> -5x + 5 = 15

Now subtract 5 from both sides:

==> -5x = 10

Now divide by -5 to free x :

==> x= 10/-5 = -2

**==> x= -2**

To check answer, substitute with x= -2 :

2x + 5 - 7x = 15

2*-2 + 5 - 7*-2 = 15

-4 + 5 +14 = 15

15 = 15

2x + 5 - 7x = 15

First, we'll combine like terms from the left side:

5 + (2x - 7x) = 15

5 - 5x = 15

Now, we'll factorize by 5, to the left side:

5(1-x) = 15

We'll divide by 5 both sides:

1 - x = 3

We'll isolate x to the lefts side. For this reason, we'll subtract 1 both sides:

-x = 3 - 1

-x = 2

We'll multiply by -1 both sides:

x = -2

**The solution of the equation is x = -2.**

We need to solve the equation 2x + 5 -7x = 15, for x.

Let's go about doing this with all the steps.

Take the equation:

2x + 5 -7x = 15

Add the terms containing x together.

=> -5x + 5 = 15

Subtract 5 from both the sides of the equation.

=> -5x + 5 - 5 = 15 - 5

=> -5x = 10

Divide both the sides of the equation by -5.

=> -5x/-5 = 10/-5

=> x = -2.

**Therefore x = -2**

2x+5-7x=15

2x and -7x on left are similars collect them together 2x-7x =-5x, and rewrite:

-5x+5 = 15.

Subtract 5.

-5x= 15-5

-5x = 10

Divide by -5.

-5x/-5 = 10/-5

x = -2.

Tally:

Put x = -2 in 2x+5-7x = 10.

LHS = 2*-2 +5 - 7*(-2)

= -4+5+14

= 1+15

= 15 = RHS